Meta-Analysis of the Effects of Rumen Protected Choline Supplementation on Milk Production and Reproduction in Dairy Cows - Prihantro, Yusuf Wili; Hartanto, Rudy; Samsudewa, Daud (ANIMAL PRODUCTION, 2025)
This study seeks to comprehensively assess the impact of Rumen Protected Choline (RPC) supplementation on key parameters in dairy cows, including dry matter intake, milk yield, milk fat and protein composition, first estrus, open days, and Service per Conception (S/C). This research utilizes a quantitative meta-analysis methodology to systematically evaluate and synthesize data. The treatment used is supplementation Rumen Protected Choline and the basal diet for control. Observed parameters include dry matter intake (DMI), milk yield (MY), milk fat content (MFC), milk protein content (MPC), service per conception (S/C), first estrus (FE), and open days (OD). The study went through five stages, namely database preparation, meta-analysis implementation, heterogeneity testing, summary effect testing, and publication bias measurement. Tools used include PDF software for filtering journals and data processing applications such as Microsoft Excel, OpenMEE Software, and Review Manager 5.4 for data interpretation. Based on the results of the meta-analysis, it is found that RPC supplementation significantly affects (p<0.05) the increase in milk production, milk protein content, and milk fat content. It is also capable of reducing S/C and open days, but it does not affect dry matter intake and first estrus. The findings of this study, derived from a meta-analysis, indicate that while RPC supplementation has no impact on feed intake, it significantly influences reproductive parameters.